A review on fumonisin and trichothecene mycotoxins in foods consumed in Turkey - (:unkn) unknown (My University, 2006)
Fumonisins are phytotoxic mycotoxins which are synthesized by various species of the fungal genus Fusarium such as F. moniliforme, F. proliferation, F. anthophilum, F. nygamai on foods like cereals. The trichothecene (TO) mycotoxins are a group of structurally similar fungal metabolites produced by various species of Fusarium, Myrothecium, Trichothecium, Stachybotrys and other fungi. Toxic TCs, as a group of naturally occurring contaminants of foods and feedstuffs and they have been detected in fungal contaminated cereal and pulse products. Fumonisins and TCs are hazardous for human and animal health. The purpose of this paper is to give a review of the papers published by the authors on the field of fumonisin and trichothecene mycotoxins in foods consumed in Turkey. 161 cereal and cereal products provided from Marmara Region were analyzed for fumonisin B1 (0.250-2.660 ppm) and B2 (not detected). 115 medicinal and herbal tea specimens provided from Istanbul market were analyzed for fumonisin B1 (0.160- 1.487 ppm) and B2 (not detected). Fumonisin B1 and B2 analyses were carried out by HPLC with fluorescence detector. Limit of detections (LOD) were 0.031 ppm and 0.468 ppm for fumonisin B1 and B1, respectively. 112 cereal and pulse products provided from Istanbul market were analyzed for T-2 toxin (0.450-4.100 ppm), 83 cereal and pulse products were analyzed for deoxynivalenol (DON) (0.140-2.670 ppm). 50 beer specimens were DON free and 65 cereal and pulse products were diacetoxyscirpenol (DAS) free. T-2 toxin and DON analyses in cereal and pulse products were carried out by HPLC with variable-wavelength UV detector. DON analyses in beer specimens were carried out by HPLC with UV-visible detector and DAS analyses were carried out by HPLC with diode array detector (DAD). All mycotoxin analyses for the entire food chain have a great importance in human health. Therefore, foodstuffs are needed to be controlled and analyzed during food process.
Keywords: Deoxynivalenol; Diacetoxyscirpenol; Fumonisins; HPLC; T-2 toxin